Strength training among professional UCI road cyclists: Practices, challenges, and rationales. - Vidar Vikestad; Idar Kristian Lyngstad; Terje Dalen (PLoS ONE)
In our study, we aimed to investigate professional road cyclists' practices in strength training, as well as their challenges with and rationales for strength training. Employing a mixed-methods approach, we collected data using a quantitative questionnaire and analysed semi-structured interviews using content analysis. After identifying professional road cyclists on FirstCycling.com's cycling statistics database, we contacted 624 cyclists by direct messaging on social media platforms, primarily Instagram. Of them, 147 professional road cyclists-88 male and 59 female-responded to the questionnaire, which we complemented with 10 semi-structured interviews to gain deeper insights into their strength training. Results revealed a common practice of engaging in two strength training sessions per week during the off- and pre-season, which dropped to one maintenance session during the race season. More female than male cyclists reported engaging in strength training during both the pre-season (96.6% vs. 85.3%) and race season (66.1% vs. 36.4%). The most significant challenges to maintaining consistent strength training were travelling, fatigue, and racing, while the primary rationales for strength training were to enhance performance, prevent injuries, and improve bone health. Moreover, the cyclists' choices in strength training seemed to be largely influenced by guidance from coaches. Altogether, our findings highlight the complexities inherent in strength training among professional cyclists and emphasise the need for expert guidance to maintain consistent practices in strength training, especially during the race season.